Human Resource Management in Improving the Quality of Education at State Primary School - Aprilia, Try Heni (LPTK UIN Syekh Wasil Kediri, 2025)
This study aims to analyse human resource management in improving the quality of education at SDN Jambean 1. The background of this study is the important role of human resource management in determining the quality of educational institutions, especially at the primary school level, which is the initial foundation for the formation of students' character and knowledge. The quality of education is strongly influenced by the effectiveness of the management of teaching and education personnel. The research method used is a descriptive qualitative method with data collection techniques through observation, interviews, and documentation. The analysis used includes data reduction, display, and data verification. The theory used is Desler’s HR implementation, which includes several aspects, including recruitment, selection, performance appraisal, and compensation. The results showed that: 1) Recruitment is carried out through stages such as announcements, initial selection, interview tests, and moral and spiritual assessments including religious moderation; 2) Selection of prospective teachers and staff follows government and internal school policy procedures, including the appointment of honorary staff to overcome the shortage of civil servants; 3) Performance appraisals focus on intention, responsibility, integrity and seriousness at work; 4) Compensation is designed with the principle of fairness, guaranteeing rewards commensurate with individual contributions to education and school management. The implications of this study show that systematic and value-based human resource management can sustainably improve the quality of education. These findings can serve as a reference for other schools in designing effective HR management policies, as well as encouraging the formulation of educational regulations that are more adaptive to the needs of educators in the field.